Pembinaan Kombinatorika bagi Mahasiswa Universitas Fajar untuk ONMIPA 2025 Bidang Matematika - Syamsuddin Mas'ud (Jurnal Abdi Bangsa, 2025)
The mentoring program for preparing students to participate in the 2025 National Mathematics and Natural Sciences Olympiad for Higher Education (ONMIPA-PT) in the field of Mathematics was conducted entirely online as an effort to enhance the mathematical abilities of Universitas Fajar students in facing the competition organized by the Ministry of Education, Culture, Research, and Technology. This program was considered important because Universitas Fajar does not yet offer an academic program specifically focused on mathematics. The students designated by the university received explanations of combinatorics material along with practice exercises aimed at ensuring their understanding of the concepts presented. Through this mentoring activity, the students gained additional insights into combinatorics topics that they had not previously encountered in their regular coursework, as well as an introduction to basic problem types commonly found in the regional selection stage. The mentoring sessions were conducted in four meetings, each with a duration of approximately two hours. The limited duration affected the depth of understanding that could be provided, and therefore, it is hoped that future preparation sessions for participating students can be optimized in terms of learning time.